Estimation of the Coastline Changes Using LIDAR - Faik Ahmet Sesli; Mustafa Caniberk (Acta Montanistica Slovaca, 2015)
In recent years, sustainable development has been a very popular subject. Sustainable development allows economic growth, social welfare and environmental protection to enhance each other. The management of environmental resources in accordance with the principles of sustainable development has become crucial in many areas including coastal resources. Integrated Coastal Zone Management is one of the tools to achieve this goal. Coastal zones involve many different elements of development and interaction and these elements change due to natural or human factors. Temporal change in coastal zones is reflected on the coast line. Coast line advance and retreat cause major changes on coastal zones. One of the most basic elements of Integrated Coastal Zone Management is the accurate determination of coastal line. For this purpose, tools such as remote sensing, photogrammetry, terrestrial measurements, GPS technology and LIDAR systems, which have been actively used in recent years, are used. In this study, the use of LIDAR technology in order to examine coastline changes was investigated. The coast line was automatically determined using LIDAR measurements of the same area from 2007, 2008 and 2009, and change analysis was made.